Modulation of stress response in Rice via genome editing of splicing factors - Abou-Raiya, Dina (AUC Knowledge Fountain, 2019)
Serine/arginine-rich (SR) proteins are a conserved family of RNA-binding proteins that act as key modulators of alternative splicing. While their functional relevance in plants remains largely unknown, a mounting evidence suggests a central role for these proteins in the response to various stresses. The work presented in this thesis sheds light on the functional significance of OsRS29 and OsRS33, two SR (arginine/serine subfamily) genes in rice as a model. In this study, genome editing using CRISPR/Cas9 system followed by RNA-seq were utilized to target two splicing factors in rice, Os-RS29 and Os-RS33 to examine the transcriptome-wide effects of these double mutants before and after salt (NaCl) treatment. Functional enrichment of the differentially expressed transcripts as well as the differentially spliced genes was done to further understand how plants are affected by salt-stress and the interplay between stress and alternative splicing. Under normal growth conditions, when compared to the wild type, the differentially expressed genes in heterozygous Os-RS29 / homozygous Os-RS33 double mutant were enriched in oxidation-reduction processes, response to stress and various plant hormone signaling pathways. On the other hand, the homozygous Os-RS29 / homozygous Os-RS33 double mutant, showed a greater impact on the expression of many genes involved in biotic and abiotic stress responsive as well as mRNA modification. After salt treatment (250mM), both double mutants displayed significant down-regulation of critical salt responsive genes rendering a sensitive response towards salt stress especially in the homozygous Os-RS29 / homozygous Os-RS33 double mutant. Since the double mutants involved two members of splice factor proteins, the alteration in the landscape of constitutive and alternative splicing (AS) was investigated. The homozygous Os-RS29 / homozygous Os-RS33 double mutant showed more decrease in the total no. of AS events than the heterozygous Os-RS29 / homozygous Os-RS33 double mutant and the wild-type. Upon exposure to salt stress, however, the no. of AS events increased dramatically in the homozygous Os-RS29 / homozygous Os-RS33 double mutant compared to the other double mutant heterozygous Os-RS29 / homozygous Os-RS33 and the wild-type. The isoform shifts under different growth conditions suggest that Os-RS33 and Os-RS29 mediate stress responses via modulating the splicing of various salt stress-responsive genes. Among the genes that showed an altered splicing the homozygous Os-RS29 / homozygous Os-RS33 double mutant are the Eukaryotic Initiation Factors (eIFs) along with some mRNA processing and splice factors. These factors were found to interact with a number of WD40-repeat proteins whose expression is changed after salt treatment. In conclusion, transcriptomic analyses of the two double mutants showed that both splicing factors play important roles in regulating various stress responses during early plant development. Further investigations of the roles of tandem repeat domain proteins in stress will provide more understanding of the mechanisms by which the plant responds to various stresses.